The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1999
DOI: 10.1074/jbc.274.16.10889
|View full text |Cite
|
Sign up to set email alerts
|

The AcbC Protein from Actinoplanes Species Is a C7-cyclitol Synthase Related to 3-Dehydroquinate Synthases and Is Involved in the Biosynthesis of the α-Glucosidase Inhibitor Acarbose

Abstract: The putative biosynthetic gene cluster for the ␣-glucosidase inhibitor acarbose was identified in the producer Actinoplanes sp. 50/110 by cloning a DNA segment containing the conserved gene for dTDP-D-glucose 4,6-dehydratase, acbB. The two flanking genes were acbA (dTDP-D-glucose synthase) and acbC, encoding a protein with significant similarity to 3-dehydroquinate synthases (AroB proteins). The acbC gene was overexpressed heterologously in Streptomyces lividans 66, and the product was shown to be a C 7 -cycli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
104
0

Year Published

2000
2000
2009
2009

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 69 publications
(108 citation statements)
references
References 36 publications
(52 reference statements)
3
104
0
Order By: Relevance
“…Earlier work has demonstrated that 2-epi-5-epi-valiolone is the precursor of the C 7 -cyclitol unit of the acarviosyl moiety of acarbose (5,8). The expectation was that a series of enzymecatalyzed steps involving dehydration, reduction, and epimerization converted this precursor to valienol (or valienamine) before its incorporation into the pseudodisaccharide acarviosine.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Earlier work has demonstrated that 2-epi-5-epi-valiolone is the precursor of the C 7 -cyclitol unit of the acarviosyl moiety of acarbose (5,8). The expectation was that a series of enzymecatalyzed steps involving dehydration, reduction, and epimerization converted this precursor to valienol (or valienamine) before its incorporation into the pseudodisaccharide acarviosine.…”
Section: Discussionmentioning
confidence: 99%
“…Acarbose can be regarded both physiologically and structurally as a member of the aminoglycoside group of bacterial products (3)(4)(5). For instance, the three subunits of streptomycin, before condensation, are either phosphorylated (streptidine 6-phosphate) or nucleotidylated (dTDP-L-dihydrostreptose or dTDP-L-rhamnose and nucleoside diphosphate-N-methyl-Lglucosamine).…”
Section: Fig 5 Tlc Analyses Of Acbm and Acbo Assays Extracts Frommentioning
confidence: 99%
See 2 more Smart Citations
“…SE50/110 (26,27). Despite its high similarity to CGTases, it has been reported that ATase has no cyclodextrin-forming activity and is not inhibited by acarbose (14).…”
mentioning
confidence: 99%